Differential Effect of Advertising Frequency on Sales Turnover and Ads to Sales Ratio - Collins C Ngwakwe, (Copernican Journal of Finance & Accounting, 2024)
This paper analysed the differential impact of repeated advertising on sales turnover and the attendant effect on accounting Ads to Sales Ratio. The paper adopts a quantitative approach and collects marketing and promoting expenditure data (as proxy for Ads activity) from Amazon Company for twenty years (2003 – 2022). The data was analysed by using the t-test of mean difference statistics and a simple regression. The t-test analysis showed that the Ads to Sales Ratio had a significant increase between two periods of comparison (2003-2012 and 2013-2022); in the same vein, there was a significant increase in mean net sales value by up to nine hundred percent – an increase which dwarfs the hundred percent increases in the Ads to Sales Ratio over the period. Furthermore, a simple regression analysis shows that marketing expenditures (used as proxy for Ads activity) produced a highly significant positive effect on net sales at a P-value of less than P<0.00001. This finding shows that current literature suggestion that increased Ads may wane consumer brand patronage may not be applicable to all industries, rather, this paper’s result indicates that for companies such as Amazon, increased Ads, or marketing and promotion activities may produce high net sales in some companies such as Amazon. The paper contributes by developing a process framework for repeated advertisement, Ads to Sales Ratio and net sales. It recommends further application of the proposed framework in related companies by future researchers.